Dissonance between the self-evaluation of professional and social standing of nurses, midwives and the evaluation made by patients and medical practitioners - Kot-Doniec, Barbara; Zarzycka, Danuta; Kiryłowicz, Ewa; Wrońska, Irena (Nursing in the 21st Century, 2013)
DISSONANCE BETWEEN THE SELF-EVALUATION OF PROFESSIONAL AND SOCIAL STANDING OF NURSES, MIDWIVES AND THE EVALUATION MADE BY PATIENTS AND MEDICAL PRACTITIONERS Aim. Identifying the contemporary social and professional standing of nurses, midwives, in the opinion of health professionals, patients and the nurses and midwives themselves. Research subjects. The study was conducted from 2009 to 2011. The study involved a total of 11,149 people, including the largest group of patients – 6,858 people, followed by nurses and midwives –2,890 respondents, and representatives of other medical professionals–1,401. Methods. The research method was a survey using an authoring diagnostic questionnaire. The number of questions in the used tool ranged from 8 to 17. Results. All groups of subjects rated the social and professional standing in both occupations at the medium level. Nurses and midwives found social and professional position at a lower level than representatives of other medical professionals and patients did. On average, about 40% of the subjects (without nurses and midwives) noted a very high and high status of surveyed professionals, while only slightly more than 20% of nurses and midwives rated their position at the highest level. Conclusions. Assessing professional and social standing of nurses and midwives at a very high and high level is typical for men, respondents aged over 60 years and below 40 years, as well as the practitioners. The factor strengthening the professional standing is competence and the evaluation of social position is mostly affected by honesty and professional integrity. The media have a negative impact on the creation of social and professional standing of nurses and midwives.